Yield and fertilizer benefits of maize/grain legume intercropping in China and Africa: A meta-analysis - (:unkn) unknown (My University, 2022)
Maize/annual grain legume intercropping is pivotal in achieving sustainable intensification in developing countries like China and some African countries. It remains unclear whether and to what extent the benefits of intercropping on crop yield and land-use efficiency vary between the two regions. This meta-analysis compared the performance of intercropping maize with six annual grain legumes (soybean, common bean, groundnut, cowpea, pea, and faba bean) commonly grown in China and Africa. Data extracted from 73 publications were used to analyze land equivalent ratio (LER), yield gain, nitrogen, and phosphorus fertilizer equivalent ratio. The overall values of LER, nitrogen, and phosphorus fertilizer equivalent ratio were significantly >1 for both China and Africa. The overall yield gain was 1.45 ± 0.07 t ha−1, with China having a higher mean (2.3 ± 0.13 t ha−1) than Africa (0.90 ± 0.07 t ha−1). Relay-strip intercropping had the highest LER and yield gain in China, while Africa’s yield gain was lower in both strip and alternate row intercropping compared with that of China. Maize/common bean intercrop had the highest yield gain in Africa, while maize/faba bean produced high yield gain in China. The yield gain for maize/peanut and maize/soybean was higher in China than in Africa. Increasing nitrogen and phosphorus rates reduced LER in both regions. Here, we show for the first time that while additional phosphorus increases yield gain for Africa it can reduce absolute yields in China. Therefore, the African farmers are recommended to adopt strip or relay-strip intercropping, common bean insertion into intercropping or moderate phosphorus fertilizer application to substantially improve yield gain and income. For China, minimizing fertilizer use by including intercropping with more legume diversity may contribute to reduced environmental problems while achieving high yield gain.
Keywords: African Research